Don't be evil how Big Tech betrayed its Founding Principles-and all of us - Rana Forooha (New York Currency, 2019)
"A penetrating indictment of how today's largest tech companies are hijacking our data, our livelihoods, our social fabric, and our minds-from an acclaimed Financial Times columnist and CNN analyst. Rana Foroohar tells the story of how Big Tech lost its soul-and ate our lunch. Through her skilled reporting and unparalleled access-won through nearly thirty years covering business and technology-she shows the true extent to which behemoths like Google, Facebook, Apple, and Amazon are monetizing both our data and our attention, without us seeing a penny of those exorbitant profits. Finally, Foroohar lays out a plan for how we can resist, by creating a framework that fosters innovation while also protecting us from the dark side of digital technology"-- Provided by publisher
Includes bibliographical references and index.
Keywords: Internet industry--Moral and ethical aspects--United States